2015
DOI: 10.1021/acs.energyfuels.5b02065
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Adhesion Force of Asphaltene Aggregates to Metallic Surfaces of Fe and Al

Abstract: Atomic force microscopy (AFM) was used to measure the adhesion force of asphaltene aggregates to metallic surfaces of aluminum (Al) and iron (Fe) at room temperature and atmospheric pressure. A simple analytical expression based on Lindhard's continuum planar potential (CPP) approximation that incorporates the effect of the surrounding fluid (a solvent) and has no fitting parameters was developed and tested with the experimental results. This expression provided predictions in good agreement with measured data. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This article focuses on the mapping of mechanical properties, with future work moving towards the use of chemical force microscopy in an effort to fully characterise samples by mapping intermolecular potentials and obtaining adhesion maps between chemically functionalised tips and samples. [23][24][25] The interaction between two surfaces across a medium is one of the fundamental issues in colloid and surface science. It is not only of fundamental interest but also of direct practical relevance when it comes to dispersing solid particles in a liquid.…”
Section: Hybrid Modementioning
confidence: 99%
“…This article focuses on the mapping of mechanical properties, with future work moving towards the use of chemical force microscopy in an effort to fully characterise samples by mapping intermolecular potentials and obtaining adhesion maps between chemically functionalised tips and samples. [23][24][25] The interaction between two surfaces across a medium is one of the fundamental issues in colloid and surface science. It is not only of fundamental interest but also of direct practical relevance when it comes to dispersing solid particles in a liquid.…”
Section: Hybrid Modementioning
confidence: 99%
“…Adsorption of asphaltenes on a wide variety of solid surfaces has been explored in the literature, including but not limited to mineral (clay, sandstone, silica, , quartz, , mica, dolomite, , montmorillonite), metal (aluminum, , gold, and iron ,,, ), metal oxides, and stainless-steel surfaces. , Langmuir-type isotherms were reported in most studies ,− when the asphaltene concentration was low or the surface had poor affinity to asphaltenes. Previous work on investigating asphaltene deposition using X-ray photoelectron spectroscopy identified different functional groups of asphaltene molecules in the single adsorbed layer and found that there was little difference in their binding energies with the metal surface …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the amount and rate of deposition are not necessarily correlated with the precipitated amount and rate of asphaltene precipitation, which is frequently observed in most onset pressure tests. Adsorption of asphaltenes on a wide variety of solid surfaces has been explored in the literature, including but not limited to mineral (clay, 13−15 sandstone, 16−18 silica, 19,20 quartz, 21,22 mica, 23−26 dolomite, 16,27−29 montmorillonite 30 ), metal (aluminum, 31,32 gold, 32−35 and iron 31,33,36,37 ), metal oxides, and stainless-steel surfaces. 32,38 Langmuir-type isotherms were reported in most studies 18,39−41 when the asphaltene concentration was low or the surface had poor affinity to asphaltenes.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies based on computational molecular simulations have made it possible to elucidate phenomenological aspects of asphaltene aggregation and their impact on viscosity. ,,,, Using model solutions to develop an atomistic description of the experimentally evaluated systems has permitted researchers to establish ideas concerning asphaltene aggregation mechanisms, ,, viscosity determinations, ,,, and other phenomena. One of the most important, and perhaps most controversial activities, is representing the entire complexity of the asphaltene fraction of crude oil in an average molecular structure or a group of molecular structures. ,, Therefore, several studies focused on proposing adequate molecular structures which allow a reliable representation of the physical behavior of a specific asphaltene type. ,,, Numerous investigations have focused on determining the mechanisms of asphaltene aggregation in n -heptane and toluene using molecular dynamics. ,,, The results indicate that asphaltene aggregation is promoted in both solvents. , Furthermore, authors have identified that the aggregation of asphaltenes in organic solvents, such as n -heptane or toluene, occurs via van der Waals type energies and the π–π interactions between the aromatic nuclei of asphaltene molecular structures. ,,, In contrast, the behavior of asphaltene molecules dissolved in polar solvents, such as water, are determined to a greater extent by electrostatic interactions and the formation of hydrogen bonds than van der Waals interactions. …”
Section: Introductionmentioning
confidence: 99%